The Leadership Role of Tapak Suci Smes Management in Increasing Student Leadership Capacity at Uin Raden Intan Lampung - Mugimanto; Ali Abdul Wakhid; Gesit Yudha (Politea : Jurnal Politik Islam, 2026)
This research is motivated by the suboptimal capacity of student leadership, characterized by low member participation in decision-making, lack of initiative, and the unstructured leadership cadre process within student organizations. This study aims to analyze the leadership role of the Tapak Suci Student Activity Unit (UKM) administrators in improving student leadership capacity at UIN Raden Intan Lampung. The research method used is field research with a descriptive qualitative approach. Data were obtained through interviews with 6 main informants and using purposive sampling criteria, observation, and documentation with informants consisting of advisors, trainers, core administrators, and active members of UKM Tapak Suci. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to test the validity of the data. The results of the study are expected to show that the leadership of the administrators plays an important role in improving student leadership capacity through coaching, cadre development, giving responsibility, exemplary behavior, and member involvement in organizational decision-making. The discussion of the research confirms that participatory and transformational leadership styles can increase self-confidence, responsibility, communication skills, active participation, and decision-making abilities of members. This research contributes to an understanding of the role of student organization leadership in developing student leadership capacity and serves as a basis for evaluation and recommendations for strengthening the cadre development and leadership development system at the Tapak Suci Student Activity Unit (UKM) of UIN Raden Intan Lampung.